2021
DOI: 10.29228/kesit.51337
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Education Program Literacy Levels of Teachers

Abstract: Bu makale İntihal.net tarafından taranmıştır. This article was checked by Intihal.net. Эта статья была проверена Интихал.нет Bu makale Creative Commons lisansı altındadır. This article is under the Creative Commons license. Это произведение доступно по лицензии Creative Commons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
1
1
0
6
Order By: Relevance
“…Aslan and Gürlen (2019) examined teachers' curriculum literacy levels and determined that the sub-factors of the curriculum literacy scale were ranked as "planning, implementation and curriculum knowledge" according to the means. This result is congruent with those of Aslan (2019), Aslan and Gürlen (2019), Atlı, Kara andMirzeoğlu (2021), Çakmak andŞinego (2021), Çetinkaya and Tabak (2019), Dedebali and Süral (2018), Demir and Toraman (2021) and Erdem and Eğmir (2018). These results confirmed that teachers and pre-service teachers are competent in curriculum literacy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Aslan and Gürlen (2019) examined teachers' curriculum literacy levels and determined that the sub-factors of the curriculum literacy scale were ranked as "planning, implementation and curriculum knowledge" according to the means. This result is congruent with those of Aslan (2019), Aslan and Gürlen (2019), Atlı, Kara andMirzeoğlu (2021), Çakmak andŞinego (2021), Çetinkaya and Tabak (2019), Dedebali and Süral (2018), Demir and Toraman (2021) and Erdem and Eğmir (2018). These results confirmed that teachers and pre-service teachers are competent in curriculum literacy.…”
Section: Discussionsupporting
confidence: 85%
“…Numerous studies have been conducted on the pre-service teachers' curriculum literacy (Aslan, 2019;Aslan & Gürlen, 2019;Atlı, Kara & Mirzeoğlu, 2021;Çetinkaya & Tabak, 2019;Demir & Toraman, 2021;Erdem & Eğmir, 2018;Şinego & Çakmak, 2021;Tunçer & Şahin, 2019). Besides, some studies were conducted on readiness for teaching (Aybek & Aslan, 2019;Karakaya, Uzel, Gül & Yılmaz, 2018;Şimşek, 2018;Yıldırım & Kalman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmaya katılan ortaokul öğretmenlerinin kendilerini yüksek seviyede eğitim programı okuryazarı olarak gördükleri söylenebilir. Alanyazın incelendiğinde bu sonuca benzer olan çalışmalara rastlanmaktadır (Aslan, 2019;Aslan & Gürlen, 2019;Atlı, Kara & Mirzeoğlu, 2021;Bayrı, 2022;Barut & Gündoğdu, 2023;Boncuk, 2021;Çetinkaya & Tabak, 2019;Dağ, 2021;Demir & Toraman, 2021;Erdem & Eğmir, 2018;Gömleksiz & Erdem, 2018;Güneş Şınego & Çakmak, 2021;Kale, 2022;Kana vd., 2018;Sarıca, 2021;Sural & Dedebali, 2018;Şahin & Aşkın Tekkol;Yılmaz & Kahramanoğlu, 2021). Ancak alanyazında bulunan bazı çalışmaların sonuçları bu araştırmanın sonuçları ile benzerlik göstermemektedir.…”
Section: Tartışma Ve Sonuçunclassified
“…Ancak alanyazında bulunan bazı çalışmaların sonuçları bu araştırmanın sonuçları ile benzerlik göstermemektedir. Kahramanoğlu (2019) (Aslan & Gürlen, 2019;Boncuk, 2021;Demir & Toraman, 2021;Güneş Şınego & Çakmak, 2021;Kahramanoğlu, 2019;Kale, 2022). Yapılan araştırmada toplam ölçek puanlarına bakıldığında en yüksek ortalamaya 21-25 yıllık öğretmenlerin, en düşük ortalamaya ise 15-20 yıllık öğretmenlerin sahip olduğu görülmüştür.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation